Implicit Motivational Processes Underlying Smoking in American and Dutch Adolescents - Larsen, Helle; Kong, Grace; Becker, Daniela; Cousijn, Janna; Boendermaker, Wouter; Cavallo, Dana; Krishnan-Sarin, Suchitra; Wiers, Reinout (Frontiers in Psychiatry, 2014)
Research demonstrates that cognitive biases toward drug-related stimuli are correlated with substance use. This study aimed to investigate differences in cognitive biases (including approach bias, attentional bias and memory associations) between smoking and non-smoking adolescents in the US and the Netherlands. Within the group of smokers, we examined the relative predictive value of the cognitive biases and impulsivity related constructs (i.e.,including inhibition skills, working memory and risk taking) on daily smoking and nicotine dependence. Method: A total of 125 American and Dutch adolescent smokers (n = 67) and non-smokers (n = 58) between 13-18 years old participated. Participants completed the smoking Approach-Avoidance Task (S-AAT), the classical and emotional Stroop task, brief Implicit Associations Task (bIAT), Balloon Analogue Risk Taking (BART), the Self-Ordering Pointing Task (SOPT) and a questionnaire assessing level of nicotine dependence and smoking behavior. Results: The analytical sample consisted of 56 Dutch adolescents (27 smokers and 29 non-smokers) and 37 American adolescents (19 smokers and 18 non-smokers). No differences in cognitive biases between smokers and non-smokers were found. Generally, Dutch adolescents demonstrated an avoidance bias towards both smoking and neutral stimuli whereas the American adolescents did not demonstrate a bias. Within the group of smokers, regression analyses showed that stronger attentional bias and weaker inhibition skills predicted greater nicotine dependence while weak working memory predicted more daily cigarette use. Conclusion: Attentional bias, inhibition skills and working memory might be important factors explaining smoking in adolescence. Cultural differences in approach-avoidance bias should be considered in future research.